Characterisation of force and torque with auxiliary heating during friction stir spot welding of AA2024-T3 - D. Tobin; S. O'Shaughnessy; D. Trimble (Results in Materials, 2024)
The peak forces generated in friction stir welding impose substantial constraints on the process window of the technology, affecting factors such as machine scale, design, and the range of applicable materials. In this study, a combination of tool force monitoring and post-weld evaluations is employed to investigate the impact of auxiliary assistive heating on various parameters including the maximum forces and torques and the effects preheating has on the microstructure and mechanical behaviours during friction stir spot welding of AA2024-T3 plates in a lap joint configuration. The methodology involves preheating the workpieces to a range of different temperatures, and the forces were measured using a dynamometer. Most notably, preheating the workpiece before the plunge stage yields a substantial reduction in peak forces. A decrease of 69 % and 76 % in vertical force and torque, respectively, was observed as the preheating temperature increased from 20 °C to 400 °C. Furthermore, the addition of auxiliary heating to the workpieces exhibited no significant statistical effect on the shear tensile performance of the resulting welds. These reductions in the process forces offer the potential for extended tool life, decreased machinery expenses, and broader material applicability, all while maintaining original joint integrity.